Single‐Electron Effects for Probing Local Electrical Polarization Changes and Charge Hopping. Issue 9 (27th June 2019) - Huth, Michael; Gruszka, Peter; Grossmüller, Christian; Hanefeld, Marc; Keller, Lukas
Abstract : Employing single‐electron effects very sensitive charge or local electrostatic potential monitoring can be accomplished. This is typically realized by single‐electron transistors operating at low temperatures. Single‐electron effects can also be used to probe local changes of the dielectric environment next to a single‐electron device. Conversely, by controlling the dielectric environment of a nanostructure subject to single‐electron effects, the electronic properties of the nanostructure can be manipulated. Here, the use of nano‐island arrays is suggested for locally probing charge, potential or dielectric changes. The authors consider small arrays for which the capacitive coupling to larger electrodes nearby causes partial screening on some of the nano‐islands. Monte Carlo simulations based on tunneling rates between next‐neighbor nano‐islands are used. This analysis is exemplarily applied to different scenarios. It is shown how surface oxidation of nano‐islands strongly influences Coulomb blockade effects. It is demonstrated how nano‐island arrays may be used to probe the dynamics of charged domain walls in the charge transfer salt tetrathiafulvalene‐chloranil. It is discussed how nano‐island arrays can be used to sense dielectric changes, e.g., in nano‐porous metal‐organic frameworks under analyte exposure. It is also discussed how the presented Monte Carlo approach can be extended from the elastic tunneling to the activated transport regime. Abstract : Single‐electron charging dominating charge transport in metallic nano‐particle arrays is employed for probing electrical polarization changes and movement of charged domain walls in dielectric materials nearby.